Social Media Responses to the Pandemic: What Makes a Coronavirus Meme Creative - Glǎveanu, Vlad Petre; de Saint Laurent, Constance (Frontiers in Psychology, 2021)
The current pandemic and the measures taken to address it, at a global scale, are unprecedented. Times of crisis call for creative solutions and these are not reduced to the work of scientists or politicians. In everyday life, both in online and offline spaces, people use their creativity to make sense of the current situation, to cope with it, and to learn its lessons. Social media is a privileged space for mundane and participative creativity through the production and sharing of coronavirus memes. In this article, we examine the creativity of such memes from a dedicated Reddit community. We ask, in particular, what makes a coronavirus meme creative and what this creativity tells us about the pandemic and popular understandings of it. To answer these questions, we use a triangulation of quantitative and qualitative methods by having 480 memes coded by three social media users for surprise, meaningfulness, elaboration, humour and creativity, and qualitatively analysing those memes that score highly on each dimension. An unexpected finding is that, when it comes to memes, creativity scores are not predicted by Reddit votes (karma votes) and, in fact, elaboration and humour are more closely related to these scores than the traditional criteria of surprise and meaningfulness. The article ends with reflections on what these findings tell us about creativity on social media more generally and the creative processes involved in the generation and reception of coronavirus memes in particular.